Magnetotelluric imaging and tectonic movement characteristics of the central Yunnan sub-block and its adjacent areas - Cui, Tengfa; Chen, Xiaobin (Science China. Earth sciences, 2023)
The central Yunnan sub-block is an important channel for southeast migration of materials in the Qinghai-Xizang Plateau, and therefore a key area to study tectonic movement and deformation. In this study, a three-dimensional electrical structure of the crust and upper mantle lithosphere was derived from magnetotelluric data inversion along a survey line across the central Yunnan sub-block. Results suggest that the middle and upper crust of the central Yunnan sub-block is comprised of several independent high-resistivity bodies. Deep extension of some faults was revealed according to electrical structure and relocated microseismicity. The Chenghai fault extends downward along the eastern boundary of a high-resistivity body. The Yuanmou fault dips to the west and extends to the depth along the boundary between two high-resistivity bodies. The Tanglang-Yimen fault cuts through a high-resistivity body in the middle and upper crust. There is an obvious high-conductivity C1 layer in the lower crust in the eastern part of the central Yunnan sub-block, and its western border displays an obvious structural boundary in the shallow part. The eastern part of the central Yunnan sub-block moves eastward relative to the western part (bounded by the west side of a high-resistivity body R3 in the C1 west). C1 is speculated to be characterized by low rheological strength and viscosity, thus reducing the resistance to eastward movement of the eastern part. Owing to the combined action of C1 and its western boundary, the eastern materials slip eastward faster relative to R3. Due to South China Block resistance, the middle and upper crust in the eastern part is within a compressional tectonic environment, consistent with the negative dilatation rate and the presence of compressive faults in this region. The C1 ground surface has a low strain rate, indicating weak deformation in this region and rigid motion dominance. Our results suggest that under the decoupling effect of the high-conductivity layer in the lower crust, the independent rigid blocks in the middle and upper crust can also exhibit tectonic deformation characteristics of rigid extrusion.